2014
DOI: 10.1016/j.jcsr.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Buckling curves for heavy wide flange QST columns based on statistical evaluation

Abstract: This paper proposes the use of existing European buckling curves to check the resistance of heavy wide flange quenched and self-tempered (QST) sections made from high-strength steel, failing by flexural buckling. The buckling curves are evaluated according to the statistical procedure given in Annex D of EN 1990 using finite element analyses. The residual stress model as described in a related paper was used to define the initial stress state of the column in the finite element model. A large database was crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…This is due to the relative amplitude of the residual stress with respect to the yield stress of the member when compared to S235 steel. Figure 6 again confirms that the imperfection factors for S460 may not be adequate, except for h/b>1.2, tf>100mm because they were recently proposed and calibrated as this range was not available in the code (Snijder et al [19], [20]). Finally, note that no cases with h/b≤1.2 and tf>100mm are included in the parametric study since no sections with these characteristics were found in catalogues.…”
Section: Results For Hot-rolled Cross Sectionsmentioning
confidence: 54%
See 2 more Smart Citations
“…This is due to the relative amplitude of the residual stress with respect to the yield stress of the member when compared to S235 steel. Figure 6 again confirms that the imperfection factors for S460 may not be adequate, except for h/b>1.2, tf>100mm because they were recently proposed and calibrated as this range was not available in the code (Snijder et al [19], [20]). Finally, note that no cases with h/b≤1.2 and tf>100mm are included in the parametric study since no sections with these characteristics were found in catalogues.…”
Section: Results For Hot-rolled Cross Sectionsmentioning
confidence: 54%
“…The recent study presented in [19], [20] about buckling curves for heavy sections was confirmed -the buckling curves chosen for sections with h/b>1,2 and tf>100mm are found suitable;…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…However, these heavy sections are available nowadays. Based on research reported in [7][8][9], Table 6.2 of EN 1993-1-1 is supplemented for these heavy sections.…”
Section: Buckling Curves For Heavy Sectionsmentioning
confidence: 99%
“…5. Finite element model to determine the flexural buckling response [9] v.11.0 implicit environment to obtain the elastic-plastic buckling response (Fig. 5) for a wide set of column configurations.…”
Section: Buckling Curves For Heavy Sectionsmentioning
confidence: 99%